1996
DOI: 10.1073/pnas.93.26.15051
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting transthyretin amyloid fibril formation via protein stabilization

Abstract: Transthyretin (TTR) amyloid fibril formation is observed systemically in familial amyloid polyneuropathy and senile systemic amyloidosis and appears to be the causative agent in these diseases. Herein, we demonstrate conclusively that thyroxine (10.8 M) inhibits TTR fibril formation efficiently in vitro and does so by stabilizing the tetramer against dissociation and the subsequent conformational changes required for amyloid fibril formation. In addition, the nonnative ligand 2,4,6-triiodophenol, which binds t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
367
0
4

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 329 publications
(378 citation statements)
references
References 42 publications
7
367
0
4
Order By: Relevance
“…Amyloid formation is also observed at the lower temperature of 25°C at pH 4.4, albeit in lower yield (20-50%). Sedimentation velocity analysis of TTR at pH 4.4 after an incubation period of 2 days at 25°C is reported in a recent publication where inhibitors of TTR amyloid formation are evaluated (28). Under these conditions, TTR exists as a mixture of sedimenting species with s values ranging from 1.6 to 6.3 S as discerned from the time derivative g(s*) analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amyloid formation is also observed at the lower temperature of 25°C at pH 4.4, albeit in lower yield (20-50%). Sedimentation velocity analysis of TTR at pH 4.4 after an incubation period of 2 days at 25°C is reported in a recent publication where inhibitors of TTR amyloid formation are evaluated (28). Under these conditions, TTR exists as a mixture of sedimenting species with s values ranging from 1.6 to 6.3 S as discerned from the time derivative g(s*) analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The sedimentation velocity profiles of wild-type TTR at pH 7.0 show the movement of a single boundary across the cell ( Figure 1A). The second moment analysis for the movement of the midpoint of the absorbance boundary (r) vs time (t) was used to obtain the apparent sedimentation coefficient, s, of 4.5 S. This s value corresponds to an s 20,w ) 4.1 S, consistent with the TTR tetramer (28). Further analysis of the data using van Hold-Weischet global fitting also indicates the presence of one single species with s 20,w ) 4.2 S ( Figure 1B,C).…”
Section: Resultsmentioning
confidence: 99%
“…The activities of diclofenac (1) analogues 2-13 as inhibitors of wild type, V30M, and L55P TTR fibril formation under conditions that simulate those found in the lysosome were determined using a stagnant fibril formation assay. 9,24 In this assay, the compound under evaluation is first incubated for 30 min with TTR at neutral pH (37°C). The pH is then lowered to give the maximal rate of fibril formation for a given variant (4.2 for wild type or 5.0 for V30M and L55P), and the samples are incubated for 72 h at 37°C.…”
Section: Resultsmentioning
confidence: 99%
“…Experiments have shown that the binding of thyroxine by TTR stabilizes the tetrameric state against acid induced dissociation, thus preventing amyloid formation in vitro. 24 Because of its hormone activity, thyroxine cannot be used to inhibit TTR fibril formation in vivo. However, focused screening and rational design efforts have resulted in the identification of several structurally diverse small molecules that, like thyroxine, bind to and stabilize TTR under fibrillogenic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Gene therapy mediated by replacing a disease-associated variant TTR/WT TTR expressing liver by a WT TTR/WT TTR expressing liver through transplantation has proven useful as a strategy for treating familial amyloid polyneuropathy (30). We have discovered small molecule TTR tetramer binders that impose kinetic stability on the tetramer, preventing dissociation required for amyloidogenesis (20,(31)(32)(33)(34). Two such small molecules are currently being tested as agents to ameliorate FAP in placebo-controlled clinical trials (see http://www.clinicaltrials.gov/).…”
mentioning
confidence: 99%